Phosphate, phytate and phytases in plants: from fundamental knowledge gained in Arabidopsis to potential biotechnological applications in wheat - David Secco (2018)
© 2017 Informa UK Limited, trading as Taylor & Francis Group. Phosphorus (P) is an essential macronutrient for all living organisms. In plants, P is taken up from the rhizosphere by the roots mainly as inorganic phosphate (Pi), which is required in large and sufficient quantities to maximize crop yields. In today’s agricultural society, crop yield is mostly ensured by the excessive use of Pi fertilizers, a costly practice neither eco-friendly or sustainable. Therefore, generating plants with improved P use efficiency (PUE) is of major interest. Among the various strategies employed to date, attempts to engineer genetically modified crops with improved capacity to utilize phytate (PA), the largest soil P form and unfortunately not taken up by plants, remains a key challenge. To meet these challenges, we need a better understanding of the mechanisms regulating Pi sensing, signaling, transport and storage in plants. In this review, we summarize the current knowledge on these aspects, which are mainly gained from investigations conducted in Arabidopsis thaliana, and we extended it to those available on an economically important crop, wheat. Strategies to enhance the PA use, through the use of bacterial or fungal phytases and other attempts of reducing seed PA levels, are also discussed. We critically review these data in terms of their potential for use as a technology for genetic manipulation of PUE in wheat, which would be both economically and environmentally beneficial.